Cuarenta años del Consejo de Estado, o de cómo seguir siendo órgano consultivo y no morir en el intento - Vera Santos, José Manuel (Revista de Derecho Político, 2018)
Resumen: Estudio de la regulación constitucional y normativa del Consejo de Estado español, desde su reconocimiento constitucional en 1978, pasando por la ley orgánica 3/1980, hasta la reforma acaecida por ley orgánica 3/2004, en los ámbitos referidos a la composición, organización interna y funciones del órgano consultivo, destacando la crítica a la última de la normas citadas, sobre todo, respecto a la regulación referida a la posible actuación del Consejo de Estado en la elaboración de propuestas normativas y de reforma constitucional. Abstract: Analysis of the constitutional and normative regulation of the Council of State from its constitutional recognition in 1978, going through the Organic Act 3/1980 to the legislative reform brought about by organic act 3/2004. Special attention will be paid to the composition, internal organization and functions of the consultative body, highlighting the critic to the afore mentioned organic act, mainly regarding the regulation referred to the possible rol of the Council of State in the development of normative and constitutional reform proposals. Summary: Introduction. 1. Normative regulation. 2. Case-law and doctrinal definition. 2.1. The Council of State as a body of constitutional importance. 2.2. The Council of State as a subsidiary body. 3. The organic act 3/1980 on the Council of State. 3.1. Composition of the Council of State. 3.2. Institutional organization. 3.3. Competences. 4. The organic act 3/2004, Reforming the organic act 3/1980 on the Council of State. 4.1. Developments concerning composition: special focus on the presence of the former Presidents of the Government as «lifelong counsellors». 4.2. Institucional developments: the creation of the Spanish Study Commission. 4.3. Functional developments: especial focus on the submission of legislative and constitutional reform proposals. Conclusions.